2021
DOI: 10.1108/wje-09-2020-0435
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations and risk assessment of heavy metals in PM2.5 from Handan, China

Abstract: Purpose This study aims to acquire a better understanding on the characteristics and risks of heavy metals (HMs) in PM2.5 from an industrial city – Handan, China. Design/methodology/approach PM2.5 samples were collected on the basis of daytime and nighttime at the state controlling air sampling site in Handan city. Ten metal elements (V, Cr, Mn, Fe, Ni, Cu, Rb, Sr, Cd and Ba) in PM2.5 were determined with an inductively coupled plasma mass spectrometry. The pollution levels of metals were characterized by en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The THQ values of the two sampling sites are both below 1, which implies the absence of non-carcinogenic risk. Hongya Niu's [108] findings are similar, but Xing Li [109] found that the non-carcinogenic and carcinogenic risks of PM pollution to children exceeded the acceptable limits in almost all cities in Hebei province. The carcinogenic risk of the PAH in particulate matter is generally higher than the acceptable limit in the North China Plain [110].…”
Section: Health Risk Assessmentmentioning
confidence: 90%
“…The THQ values of the two sampling sites are both below 1, which implies the absence of non-carcinogenic risk. Hongya Niu's [108] findings are similar, but Xing Li [109] found that the non-carcinogenic and carcinogenic risks of PM pollution to children exceeded the acceptable limits in almost all cities in Hebei province. The carcinogenic risk of the PAH in particulate matter is generally higher than the acceptable limit in the North China Plain [110].…”
Section: Health Risk Assessmentmentioning
confidence: 90%
“…Handan is bordered by the Taihang Mountains to the west and the North China Plain to the east and belongs to China's Third Ladder; the terrain is high in the west and low in the east, which is not conducive to the diffusion of air pollutants (Figure 1). Moreover, Handan is located at the junction of the four major provinces (Hebei, Henan, Shandong, and Shanxi) with intense pollutant emissions in China, and the air pollution is serious [27]. Hence, it is easy to increase the interregional transport of air pollutants.…”
Section: Study Areamentioning
confidence: 99%
“…According to statistics in 2020, the total storage capacity of coal gangue in China has exceeded 6 billion tons, and more than 2600 gangue hills have been formed 39 . Gangue hills are a waste of land resources, and their long‐term weathering causes great environmental pollution and natural disasters, such as rain erosion, spontaneous combustion, collapse, and debris flow 40–42 . Therefore, coal gangue needs to be recycled.…”
Section: Introductionmentioning
confidence: 99%
“…39 Gangue hills are a waste of land resources, and their long-term weathering causes great environmental pollution and natural disasters, such as rain erosion, spontaneous combustion, collapse, and debris flow. [40][41][42] Therefore, coal gangue needs to be recycled. At present, coal gangue has been used in backfill materials, geotechnical engineering, 43 agriculture, 44 building materials, 45 ion adsorption, 46 concrete-modified materials, 47 porous materials, 48 extract valuable metal, 49 but its comprehensive utilization rate is still low.…”
Section: Introductionmentioning
confidence: 99%